A Two-Year, Prospective, Blinded Analysis of Complications Following Peripheral Nerve Blocks in Foot and Ankle Surgery. Issue 1 (19th August 2016) - Kunas, Grace C.; Curren, Jodie; Ford, Carey; Fields, Kara; YaDeau, Jacques; Kahn, Richard; Ellis, Scott J.
Category: Other Introduction/Purpose: Previous data shows complications related to peripheral nerve blocks (PNBs), the standard of care in anesthesia for foot and ankle surgery, occur infrequently. Elucidating the extent of these complications after lower extremity procedures will help improve the safety and quality of care delivered. The purposes of this study were to report the incidence and type of PNB-related complications, and to understand how the type of PNB, specifically popliteal and ankle blocks, may affect these complications. This is the largest prospective study to date and the first to review complications in a blinded fashion by both an unassociated surgeon and anesthesiologist. We hypothesized complications would be rare and mostly resolvable. Methods: Patients undergoing foot and ankle surgery with a PNB were prospectively enrolled for two years and followed postoperatively for three months or until the resolution of complications. Surgery time, tourniquet time, and demographics (age, BMI, sex, comorbidities, and number of surgeries) were collected. A survey was filled out by surgeons at all postoperative visits, and detailed the nature and anatomic location of perioperative complications. Complications were reviewed independently and blindly both by a surgeon and anesthesiologist unassociated with the case and rated as 1) likely from the nerve block, 2) possibly due to the block, or 3) definitely not from the block. Serious complications were defined as those needing an intervention or having a motor deficit, numbness/pain not resolved after 6 weeks, or pain or neuropraxia outside the surgical site. Results: 2, 516 patients undergoing 2, 704 foot and ankle procedures from October 8, 2012 to October 7, 2014 were identified. Of these, 287 patients (11.4%) had a total of 290 (10.7%) complications after surgery. The majority of surgeries were performed with popliteal block (see table). Complications possibly due to the block were significantly higher in those with a popliteal compared to an ankle block (p < 0.001), but no difference in the complications likely due to the block was found (p=0.522). In complications at least possibly due to the block, dexamethasone additive was a significant predictor (p < 0.001). None of the demographic factors were associated with complications. Interrater agreement between the surgeon and anesthesiologist was found to be 0.42 (weighted kappa statistic), representing agreement on 64.6% of causes of the complications. Twenty serious complications occurred in the 112 possibly block-related complications, 16 of which were unresolved. Conclusion: These findings suggest that the use of PNB in foot and ankle surgery is associated with a low post-operative complication rate and few serious, unresolved complications, most being neurological in nature. The majority of were not attributable to PNBs, but more of the complications possibly due to the block were attributable to popliteal blocks than ankle blocks. The small number of complications made it difficult to draw conclusions about confounders. The relative lack of agreement between the surgeon and anesthesiologist suggests that the cause of complications is commonly not obvious which creates difficulty in studying and managing these patients.